Hubungan Disiplin Anggota Tentera Darat Malaysia (TDM) di Kawasan Lembah Klang dengan Faktor Agama - Zainol Abidin, Zahimi (2011)
This study had been conducted to identify the relationship between religious factors which declined the discipline of the Malaysian Army (TDM) members in the Klang Valley. This study was conducted in a number of military camps located in the Klang Valley which includes the Federal Territory of Kuala Lumpur and Selangor. Respondents consisted of 240 members who were identified in TDM particularly in Klang Valley who was involved in various offenses during the term of their services. The Research instrument used in the study was an adaptation of the questionnaire used by K. Shoba (2007) Saidi (2006), and Sayed Mahussain (2007 in their study of student discipline problems and discipline in military which involved military personnel. The questionnaire used was modified according to the needs of this study. The degree of reliability (Cronbach alpha) for the whole of the instruments used in the study was .932. The data gathered was analyzed using the Statistical Software Package for Social Science (SPSS) version 1 7. Descriptive analysis is used to analyze the frequency, percentage, mean and standard deviation. The survey, conducted using Pearson correlation showed significant relationship between education parents and families, religious knowledge, religious activities and attitudes of team members of the religious practices of TDM with the decline of discipline in the Klang Valley. Through multiple regression test found a signiJicant influence of religious factors and the decline of discipline in the TDM in the Klang Valley. In the test found that three variables: parental education and family, Islamic knowledge and attitudes towards religion has a negative influence on the decline in discipline and one variable which is religious activities in the unit have a positive influence on the decline in discipline of the Malaysian Army (TDM) members in the Klang Valley.